FACTORS RELATED TO THE CAUSE OF TUBERCULOSIS (TB) IN CHILDREN - Ningsih, Nurna; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Tuberculosis (TB) is an infection brought about by the intricate living being Mycobacterium tuberculosis, which incorporates M. africanum, M. bovis, and M. canetti (and others that don't influence people). The aim of this research is to find out factors related to the cause of tuberculosis in children. This study reviews the literature using electronic data from several original studies. Online resources for finding literature include Science Direct and Google Scholar. keyword research used were